ANALYSIS OF THE EFFECTS OF DROUGHT ON TIME RESPONSE OF VEGETATION INDEX NORMALIZED DIFFERENCE (NDVI) IN THE STATE OF AMAZONAS - Paiva, Célia Maria (2016)
Vegetation indices derived by remote sensing can help identify occurrence of drought on a regional scale. The Normalized Difference Vegetation Index (NDVI) has been widely used in vegetation monitoring, with promising results. This study aims to identify the patterns of temporal response of NDVI in relation to occurrence of deficit/surplus water to different regions of the Amazon biome, as well as understand its seasonal and inter-annual cycles. Therefore, data from five weather stations of the National Institute of Meteorology (INMET) and a set of orbital data of  EFAI-NDVI were used. The study period covers the years 1982 to 1990. The results indicate that the response of NDVI to the occurrence of drought is one month in all regions. In the case of water surplus, that response varies from one to four months. Seasonally, the highest NDVI values occur after the rainy season in the region and the lowest values occurring after the dry season. On inter-annual behavior, the NDVI decreases in El Niño years and rises in La Niña years.